Efektivitas Imbauan Waktu Salat Terhadap Kesadaran Salat Berjamaah Bagi Mahasiswa Fakultas Dakwah Universitas Islam Bandung - Bintang Muhammad Zuladha Tarigan; Rodliyah Khuza’i; Hendi Suhendi (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. Congregational prayer has the urgency of fiqh as a way of guidance and social urgency as a symbol of togetherness of Muslims. However, the application of congregational prayers is not optimal in this technological era. At the Islamic University of Bandung, there is an appeal for prayer times, aiming to encourage the academic community to carry out congregational prayers. However, the phenomenon that occurred was still found by students of the Faculty of Da'wah class of 2020 ̶ 2022 who crowded in the campus environment. This study measures the effectiveness of prayer time appeals on congregational prayer awareness of students of the Faculty of Da'wah class of 2020-2022. The research methods used are quantitative with data analysis techniques such as validity tests, reliability tests, classical assumption tests, simple linear regression analysis, determination coefficient tests, and hypothesis tests. The results of the study showed that the significance value of the hypothesis test was 0.001 < 0.05, so that Ho was rejected and Ha was accepted. This means that the prayer time appeal is effective in increasing awareness of congregational prayer with a determination coefficient of 46.1%, although not significant. Students of the Faculty of Da'wah class of 2020-2022 have a very good understanding of prayer time appeals and congregational prayer awareness. Abstrak. Salat berjamaah memiliki urgensi fiqih sebagai jalan petunjuk dan urgensi sosial sebagai simbol kebersamaan kaum muslimin. Namun, penerapan salat berjamaah kurang optimal di era teknologi ini. Di Universitas Islam Bandung, terdapat imbauan waktu salat, bertujuan untuk mendorong sivitas akademika melaksanakan salat berjamaah. Namun, fenomena yang terjadi, masih ditemukan mahasiswa Fakultas Dakwah angkatan 2020 ̶ 2022 yang berkerumun di lingkungan kampus. Penelitian ini mengukur efektivitas imbauan waktu salat terhadap kesadaran salat berjamaah mahasiswa Fakultas Dakwah angkatan 2020-2022. Metode penelitian yang digunakan adalah kuantitatif dengan teknik analisis data seperti, uji validitas, uji reliabilitas, uji asumsi klasik, analisis regresi linier sederhana, uji koefisien determinasi, dan uji hipotesis. Hasil penelitian menunjukkan nilai signifikansi uji hipotesis 0.001 < 0.05, sehingga Ho ditolak dan Ha diterima. Ini berarti imbauan waktu salat efektif dalam meningkatkan kesadaran salat berjamaah dengan koefisien determinasi 46,1%, meskipun tidak signifikan. Mahasiswa Fakultas Dakwah angkatan 2020-2022 memiliki pemahaman imbauan waktu salat dan kesadaran salat berjamaah yang sangat baik.